Calculation of discrete correlation functionin facet systems of techical vision - Volodymyr Borovytsky; Vadym Antonenko (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The paper proposes a facet vision system composed from identical facet elements. Each facet element contains an optical system, several photodetectors, a preamplifier, and a universal microcontroller. In such a system, all facet elements operate independently of each other. Each facet element performs fast measurements of the angular velocity of objects in its field of view by calculating the discrete correlation functions of the signals from the photodetectors. The paper considers the possibility of using economical microcontrollers in facet elements for fast calculation of the discrete correlation functions. The authors perform a comparative analysis of the techniques based on the direct calculation and the calculation with fast Fourier transform. The investigation of the corresponding program code for microcontrollers in assembly language is done with calculations of the number of machine instructions and their execution time. The study confirms that economical universal microcontrollers are able to perform fast measurements by finding the maximum values of discrete correlation functions. In the case of receiving signals from 4 photodetectors, the calculation time is less than 10 milliseconds for input data arrays of 384 elements and less than 1.2 milliseconds for input data arrays of 128 elements. These results make the proposed facet vision systems applicable in navigation, orientation, and collision avoidance with moving and stationary objects in automatic vehicles, including unmanned aerial vehicles.